KECANDUAN GAME ONLINE DENGAN INSOMNIA PADA REMAJA - Mais, Fraldy Robert; Rompas, Sefti S.J.; Gannika, Lenny (JURNAL KEPERAWATAN, 2020)
Abstract: Online games are a means of entertainment that is often used by Adolescents. Excessive use of this online game can make the users become addicted to online games. Adolescents  who are addicted to playing online games will use their time to play, and forgot other activities like taking a rest and sleeping. it can make them experience insomnia sleep disorders. The purpose of this research is to find out the relationship between online game addiction with insomnia in adolescent in Senior High School 1 Tondano. This research used descriptive analytic with Cross Sectional Study approach. The sampling technique used purposive sampling, with a total sample of 68 adolescents. The results of statistical test studies using Spearman test at a significance level of 95% or α = 0.05, obtained a significant value, r = 0.003 <α = 0.05. Conclusion there is a significant relationship between online game addiction with insomnia in adolescents. Suggestions are expected for schools and parents to supervise teenagers in playing online games, and for teens to improve their self-control in playing online games and pay attention to time to rest and sleep.Key Words : Online Game Addiction, Insomnia, Adolescent Abstrak: Game online merupakan suatu sarana hiburan yang sering digunakan oleh para remaja. Penggunaan yang berlebihan terhadap game online ini dapat menyebabkan para penggunanya mengalami kecanduan game online. Remaja yang mengalami kecanduan dalam bermain game online akan menggunakan waktunya untuk bermain, sehingga mereka melupakan aktivitas  istirahat dan tidur. hal tersebut dapat membuat mereka mengalami gangguan tidur insomnia. Tujuan untuk mengetahui hubungan antara Kecanduan game online dengan insomnia pada remaja di SMA N 1 Tondano. Desain Penelitian yang digunakan yaitu Deskriptif Analitik  dengan pendekatan Cross Sectional Study. Teknik pengambilan sampel menggunakan Purposive Sampling, dengan jumlah sampel sebanyak 68 remaja. Hasil Penelitian uji statistik menggunakan uji Spearman pada tingkat kepercayaan 95% atau α = 0,05, didapatkan nilai r = 0,003 < α = 0,05. Kesimpulan terdapat hubungan yang signifikan antara kecanduan game online dengan insomnia pada remaja. Saran diharapkan bagi pihak sekolah dan orang tua untuk mengawasi para remaja dalam bermain game online, dan untuk remaja agar supaya dapat meningkatkan kontrol diri dalam bermain game online serta memperhatikan waktu untuk istirahat dan tidur.                       Kata Kunci : Kecanduan Game online¸Insomnia, Remaja